Differences in Muscle Protein Synthesis and Anabolic Signaling in the Postabsorptive State and in Response to Food in 65–80 Year Old Men and Women - Smith, Gordon I.; Atherton, Philip; Villareal, Dennis T.; Frimel, Tiffany N.; Rankin, Debbie; Rennie, Michael J.; Mittendorfer, Bettina (PLOS ONE, 2008)
Women have less muscle than men but lose it more slowly during aging. To discover potential underlying mechanism(s) for this we evaluated the muscle protein synthesis process in postabsorptive conditions and during feeding in twenty-nine 65–80 year old men (n = 13) and women (n = 16). We discovered that the basal concentration of phosphorylated eEF2Thr56 was ∼40% less (P<0.05) and the basal rate of MPS was ∼30% greater (P = 0.02) in women than in men; the basal concentrations of muscle phosphorylated AktThr308, p70s6kThr389, eIF4ESer209, and eIF4E-BP1Thr37/46 were not different between the sexes. Feeding increased (P<0.05) AktThr308 and p70s6kThr389 phosphorylation to the same extent in men and women but increased (P<0.05) the phosphorylation of eIF4ESer209 and eIF4E-BP1Thr37/46 in men only. Accordingly, feeding increased MPS in men (P<0.01) but not in women. The postabsorptive muscle mRNA concentrations for myoD and myostatin were not different between sexes; feeding doubled myoD mRNA (P<0.05) and halved that of myostatin (P<0.05) in both sexes. Thus, there is sexual dimorphism in MPS and its control in older adults; a greater basal rate of MPS, operating over most of the day may partially explain the slower loss of muscle in older women.